2004
DOI: 10.1097/01.prs.0000129075.96217.92
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Sprouting Occurs following End-to-Side Neurorrhaphy

Abstract: Recent evidence supports the use of end-to-side neurorrhaphy for the treatment of certain peripheral nerve disorders. However, the mechanism by which nerves regenerate following this procedure is still unclear. To address this question, the authors designed a new end-to-side coaptation model in rats in which the donor nerves were uninjured. The regenerated axons at the coaptation site were observed directly using fluorescent dye as the neural tracer. The sciatic nerve from adult Wistar rats was transplanted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 30 publications
2
45
0
6
Order By: Relevance
“…The precise mechanism of axonal regeneration following end-to-side neurrorhaphy remains controversial with both experimental and clinical studies reporting mixed results [4,6,8,11,12,19,20,[23][24][25][33][34][35][36][37]. Several authors have concluded that axonal damage to the donor nerve is required to induce motor collateral sprouting but may not be required to induce sensory sprouting in end-to-side neurorrhaphy [1,12,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of axonal regeneration following end-to-side neurrorhaphy remains controversial with both experimental and clinical studies reporting mixed results [4,6,8,11,12,19,20,[23][24][25][33][34][35][36][37]. Several authors have concluded that axonal damage to the donor nerve is required to induce motor collateral sprouting but may not be required to induce sensory sprouting in end-to-side neurorrhaphy [1,12,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The other is that regenerated nerve derived from terminal sprouting of donor nerve due to the damage to the donor nerve during suturing process [56][57][58]. Zhang, et al [59] and Hayashi, et al [60] demonstrated that the nerve regeneration through the terminolateral neurorrhaphy originated from the collateral sprouting from the intact donor nerve by using immunofluorescence tracing technique. However, Hastert, et al [61] founded that nerve regeneration not only originated from collateral sprouting from noninjurious donor nerve, but also originated from terminal sprouting from the damaged donor nerve when retrograde nerve tracing of neurons performed with DiI and FluoroGold to reveal the origin of regenerated axons through sciatic nerve in a rat model.…”
Section: The Mechanism Of Nerve Regeneration Of Terminolateral Neurormentioning
confidence: 99%
“…1), any mechanical damage to the donor nerve was avoided by employing a non-injurious technique of endto-side nerve coaptation previously described by Hayashi et al 55 Proximal end of the recipient nerve segment was split longitudinally by microscissors, and its split ends were completely wrapped around the donor nerve and then sutured together by four No. 11-0 Ethilon sutures.…”
Section: Experimental Design and Surgical Proceduresmentioning
confidence: 99%